2023
DOI: 10.1093/postmj/qgad024
|View full text |Cite
|
Sign up to set email alerts
|

The association between mortality and door-to-antibiotic time: a systematic review and meta-analysis

Abstract: Purpose Previous studies evaluating the impact of antibiotic timing on mortality in sepsis have shown conflicting results. We performed a meta-analysis to evaluate the association between door-to-antibiotic time (each hour of delay) and mortality in sepsis. Methods We searched PubMed and Embase through 10 November 2022 to identity cohort studies that evaluated the adjusted association between door-to-antibiotic time (each hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…In these cases, timely and appropriate antimicrobial treatment is crucial. Studies have shown that delays in starting such treatment, or the use of inappropriate antimicrobial regimens, are linked to increased mortality rates (2)(3)(4)(5)(6)(7)(8). Despite the well-recognized importance of early and appropriate antibiotic therapy in managing sepsis, adherence to this principle has been disappointingly low.…”
Section: Introductionmentioning
confidence: 99%
“…In these cases, timely and appropriate antimicrobial treatment is crucial. Studies have shown that delays in starting such treatment, or the use of inappropriate antimicrobial regimens, are linked to increased mortality rates (2)(3)(4)(5)(6)(7)(8). Despite the well-recognized importance of early and appropriate antibiotic therapy in managing sepsis, adherence to this principle has been disappointingly low.…”
Section: Introductionmentioning
confidence: 99%